2021
DOI: 10.3390/rs13214317
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Adaptive Kalman Filter for a Single Frequency GNSS/MEMS-IMU/Odometer Integrated Navigation Module

Abstract: Aiming at the GNSS receiver vulnerability in challenging urban environments and low power consumption of integrated navigation systems, an improved robust adaptive Kalman filter (IRAKF) algorithm with real-time performance and low computation complexity for single-frequency GNSS/MEMS-IMU/odometer integrated navigation module is proposed. The algorithm obtains the scale factor by the prediction residual, and uses it to adjust the artificially set covariance matrix of the observation vector under different GNSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The size of R k reflects the size of the measurement noise. According to equation (14), in the innovation-based adaptive Kalman filtering algorithm, the value of R k will change with the change of innovation v k and time t. Therefore, in the kth moment and the k − 1th moment, the change of the innovation |v k − v k−1 | can reflect whether the measurement noise appears abnormal, if the value of the change is larger, it means that the measurement signal is subject to the greater noise interference.…”
Section: Introduction Of Window Opening Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of R k reflects the size of the measurement noise. According to equation (14), in the innovation-based adaptive Kalman filtering algorithm, the value of R k will change with the change of innovation v k and time t. Therefore, in the kth moment and the k − 1th moment, the change of the innovation |v k − v k−1 | can reflect whether the measurement noise appears abnormal, if the value of the change is larger, it means that the measurement signal is subject to the greater noise interference.…”
Section: Introduction Of Window Opening Methodmentioning
confidence: 99%
“…Wang proposed an adaptive federal Kalman filtering algorithm based on variable fractional Bayes in the literature [13] and applied it to an INS/GPS/topographic/geomagnetic multi-source navigation system, which was experimentally shown to improve the positioning accuracy relative to the conventional federal filter under time-varying or even unknown MNCM conditions. To address the vulnerability of Global navigation satellite system (GNSS) receivers in urban environments and the low power consumption of integrated navigation systems, Yan proposed an improved robust adaptive Kalman filtering algorithm for single-frequency GNSS/MEMS-IMU/odometer integrated navigation modules with good real-time performance and low computational complexity in the literature [14]. Wang proposed a multifading factor-based adaptive Kalman filtering algorithm in the literature [15], which uses a time-varying adaptive fading factor to modify the filter parameters online and design a Kalman filter for the SINS/GPS system to enhance the robustness of the system under extreme external environments.…”
Section: Introductionmentioning
confidence: 99%
“…From the aforementioned research, it can be concluded that the quality of observation values of low-cost smart terminals is poor, and abnormal data processing needs to be performed in terms of data preprocessing and quality control to improve positioning performance. In view of that, this research studied robust estimation in smart terminal data processing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mahalanobis distance (MD) is an index for anomaly statistical detection [ 22 ]. The robust estimate approach can be used for robust filtering when the observation value is abnormal, which can successfully lessen the impact of abnormal model deviation and abnormal measurement [ 23 ].…”
Section: Introductionmentioning
confidence: 99%